Einig in der Theologie der Ämter? das Amtsverständnis in Lumen Gentium aus der Sicht der orthodoxen Theologie - Vletsis, Athanasios 1956- (2015)
In »Unitatis redintegratio« the Roman-Catholic church accepts the office and the sacraments of the Oriental churches. On this basis, the article explores whether the Orthodox church can say the same about the theology of office and the sacraments of the Roman-Catholic church presented in »Lumen gentium«. It, then, discusses what both churches have in common and where the differences are. The final section marks the open tasks that still hinder a consensus between the two churches.
Keywords: Amtsverständnis; Amtsgewalt